2003
DOI: 10.1016/j.neuroimage.2003.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The brain basis of syntactic processes: functional imaging and lesion studies

Abstract: Language comprehension can be subdivided into three processing steps: initial structure building, semantic integration, and late syntactic integration. The two syntactic processing phases are correlated with two distinct components in the event-related brain potential, namely an early left anterior negativity (ELAN) and a late centroparietal positivity (P600). Moreover, ERP findings from healthy adults suggest that early structure-building processes as reflected by the ELAN are independent of semantic processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
191
3
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(230 citation statements)
references
References 59 publications
26
191
3
5
Order By: Relevance
“…Yet many sentence processing studies have argued that the middle temporal gyrus is involved in semantic integration processes consistent with the second interpretation of the results (Friederici and Kotz, 2003;Kuperberg et al, 2005;Baumgaertner et al, 2002). Although it is possible that PMTG processes both combinatorial and lexical semantic aspects of verbs, more evidence is required.…”
Section: Discussionmentioning
confidence: 51%
“…Yet many sentence processing studies have argued that the middle temporal gyrus is involved in semantic integration processes consistent with the second interpretation of the results (Friederici and Kotz, 2003;Kuperberg et al, 2005;Baumgaertner et al, 2002). Although it is possible that PMTG processes both combinatorial and lexical semantic aspects of verbs, more evidence is required.…”
Section: Discussionmentioning
confidence: 51%
“…The shift of focus within STG to more posterior portions in response to written sentences may reflect slower, more controlled integration processes for written than spoken sentences. Such an interpretation would be supported by work coming from patient studies, showing that lesions in the posterior portion of the temporal lobe hamper late integration (Friederici and Kotz, 2003). It is suggested that the anterior STG supports the establishment of phrase structure expectancies, which are not fulfilled upon encountering a grammatically impossible word in a previously established sentence structure.…”
Section: Modality Effects In Sentence Processingmentioning
confidence: 92%
“…The anterior portion of the STG has been shown to come into play, in particular, when syntactic aspects during auditory sentence processing are required (Friederici et al, 2000a). The finding that the anterior STG is involved in on-line syntactic processing in the auditory domain is, moreover, supported by a lesion study indicating that fast syntactic processes are missing in patients with lesions in the anterior portion of the temporal lobe (Friederici and Kotz, 2003) and by an MEG study in which the fast syntactic processes were reflected by two dipoles in the left hemisphere, one of which was located in the anterior STG (Friederici et al, 2000c). The shift of focus within STG to more posterior portions in response to written sentences may reflect slower, more controlled integration processes for written than spoken sentences.…”
Section: Modality Effects In Sentence Processingmentioning
confidence: 92%
See 1 more Smart Citation
“…Specifically, we were interested in the nature of the cortical systems that compute syntactic representations during online language comprehension. Three regions have traditionally been identified as candidates for syntactic processing (Fedorenko et al, 2012;Friederici and Kotz, 2003;Grodzinsky and Friederici, 2006;Kaan and Swaab, 2002). Historically, Broca's area or left inferior frontal gyrus (IFG) has been most associated with syntax (Ben-Shachar et al, 2003;Ben-Shachar et al, 2004;Bornkessel-Schlesewsky et al, 2009;Caplan et al, 2008;Caplan et al, 2000;Carramazza and Zurif, 1976;Dapretto and Bookheimer, 1999;Embick et al, 2000;Friederici et al, 2006;Grodzinsky, 2001;Just et al, 1996;Santi and Grodzinsky, 2007;Stromswold et al, 1996).…”
Section: Introductionmentioning
confidence: 99%